Сфрагістика козацької України: стан, здобутки, перспективи - Ситий, І. (Сiверянський лiтопис, 2014)
У статті аналізується стан, здобутки, перспективи української сфрагістики
доби козаччини. В статье анализируются достижения и перспективы развития украинской сфрагистики времен Гетманщины. The achievements and perspectives of the Ukrainian sphragistics of Cossack Hetmanat
times are analysed in the article.